Biogas production by anaerobic digestion of wastewater from palm oil mill industry - Nabarlatz, Debora Alcida; Arenas Beltrán, Ligia Patricia; Herrera Soracá, Diana Milena; Niño Bonilla, Diana Andrea (CT&F - Ciencia, Tecnología y Futuro, 2013)
The environmental impact caused by the fossil fuel use encourages society to look for new sources of renewable energy, such as biodiesel. During the last years, palm oil production has dramatically increased in Colombia, since it is the main raw material for biodiesel production. As consequence of the process, palm oil mill effluents with high content of pollutants are released to the environment. Since these effluents have physicochemical characteristics that make them suitable for the production of biogas by anaerobic digestion of residual water, this research evaluates the production of methane using wastewater as substrate from a Colombian palm oil mill. Anaerobic digestion experiments were conducted in batch mode to evaluate the influence of pH and inoculum to substrate ratio, by using two differents inoculums. It was found that the most suitable inoculum was a mixture of 1:1 v/v urban Wastewater Treatment Plant (WWTP) anaerobic sludge/pig manure at a ratio 2 g Volatile Solids (VS) inoculum/g VS substrate, which presented the highest accumulated methane production, reaching 2740 mL methane (0.343 m3 CH4/kg VS) without neutralizing pH.